Indústria 4.0 - projeto de implementação de IoT: oportunidades e desafios no setor de manufatura - Piccirillo, Kátia Diniz da Silva (2024)
This study sought to study the opportunities and challenges arising from Internet of Things (IoT) implementation projects in the context of Industry 4.0, focusing on the manufacturing sector, particularly in two micro-enterprises in the state of São Paulo. The research was conducted using a mixed-methods approach, combining qualitative and quantitative data collected through semi-structured interviews and forms applied to managers and experts in the field. The results reveal that IoT offers several opportunities for optimizing industrial processes, such as increasing operational efficiency, reducing costs, and improving the reliability of data used in operations. The ability to make more assertive decisions based on real-time data was also one of the main benefits highlighted by the participants. However, the study also identified significant challenges to the adoption of IoT, including the lack of government incentives, the high initial investment required for the implementation of IoT technologies. In addition, the lack of robust technological infrastructure and the shortage of qualified professionals are factors that can hinder the digitalization process of companies. The study concludes that, although challenges exist, the adoption of IoT can bring significant competitive advantages, as long as companies are willing to invest in training, infrastructure and an internal cultural change. The contributions of this research are relevant for both business managers and public policy makers, as they provide a detailed understanding of the conditions necessary to facilitate the transition to Industry 4.0. In addition, the knowledge generated can be used to develop strategies to overcome the challenges to IoT adoption and maximize opportunities for innovation and competitiveness in the manufacturing sector.